2021
DOI: 10.1007/s11581-021-04148-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel cobalt and strontium-free perovskite Pr0.5Ba0.5Fe1-xNixO3-δ (x=0 and 0.2) as cathode for intermediate-temperature solid oxide fuel cells

Abstract: The sol-gel method was adopted to synthesize novel cobalt and strontium-free Pr 0.5 Ba 0.5 Fe 1-x Ni x O 3-δ (x = 0 and 0.2, abbreviated as PBF and PBFN) perovskite oxides. It was aimed to discuss the influence of B-site Ni substitution on structure and electrochemical properties of Pr 0.5 Ba 0.5 FeO 3-δ . The results indicated that PBF-based oxides were both cubic perovskite structure. Ni atoms were successfully doped into the B sites of PBF, resulting in lattice shrinkage. Ni doping could enhance the oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 °C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1). The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 • C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 °C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1). The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 • C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1).…”
Section: Resultsmentioning
confidence: 67%
“…The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 °C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1). The power density of the SOFC with the thin GDC electrolyte is compared with the SOFC performance within 700-800 • C reported in [31][32][33][34], which further illustrates its excellent performance (see Table 1). Thus, the advantages of a single-layer GDC electrolyte over a single-layer YSZ electrolyte are recognized not only at low temperatures (600-650 • C) but also at relatively high operating temperatures of ~800 • C. For example, in using the cobalt-containing oxide cathode in the range of 750 to 800 • C, a single-layer YSZ electrolyte requires the formation of a barrier layer near the cathode.…”
Section: Resultsmentioning
confidence: 67%
“…As shown in Figure 2b, the characteristic spectrum of O 1s presented two peaks at 528.78 and 531.27 eV. 23 The peak with a lower binding energy was classified as lattice oxygen, and that with a higher binding energy was classified as adsorbed oxygen. The peak at the bond energy of 685 eV (Figure 2c) was classified as F 1s, which indicates that the valence state of F in SFS 0.1 F 0.1 was −1.…”
Section: Resultsmentioning
confidence: 98%
“…Pr 0.5 Ba 0.5 FeO 3− δ (PBF) has been used as the cathode material of SOFCs, and has achieved high electrochemical performance. 34 This work has developed Pr 0.5 Ba 0.5 Fe 0.8 Ni 0.2 O 3− δ (PBFN) as a highly active SSOC electrode material, which can achieve high electrochemical performance. Experiments showed that the electrocatalytic activity was enhanced by the exsolution of Ni–Fe alloy nanoparticles and the concomitant phase transition from the single cubic (Pr 0.5 Ba 0.5 FeO 3− δ ) to A-site ordered double perovskite (PrBaFe 2 O 5+ δ ), which could increase the concentration of oxygen vacancies and the reactive sites.…”
Section: Introductionmentioning
confidence: 99%